2021
DOI: 10.1055/s-0041-1736340
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Smartphone in the Diagnosis of Vestibular Hypofunction: A Clinical Strategy for Teleconsultation during the COVID-19 Pandemic and Beyond

Abstract: Introduction Vestibular disorders (VDs) are highly prevalent in primary care. Although in general they comprise conditions that are not life-threatening, they are associated with significant functional and physical disability. However, the current coronavirus disease 2019 (COVID-19) pandemic has imposed limitations on the standard treatment of benign conditions, including VDs. In this context, other resources may aid in the diagnosis and management of patients with VDs. It is well known that teleconsultation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Face-to-face physician-patient interaction will always be important. However, several researchers have observed a gradual path for the medical specialties to learn how to reach their patients remotely and benefit from it [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face physician-patient interaction will always be important. However, several researchers have observed a gradual path for the medical specialties to learn how to reach their patients remotely and benefit from it [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank the editor for the opportunity to respond to the issues raised by a reader related to our paper. 1 To apply any procedure or tool in any specialty, it is necessary to master the technique by prior training, and this is no different with teleservice. Each professional must always seek to improve their skills to perform procedures optimally.…”
mentioning
confidence: 99%
“…We would like to thank the editor for the opportunity to respond to the issues raised by a reader related to our paper. 1…”
mentioning
confidence: 99%
“…Barreto et al concluded that "The creation of a digital vestibular management algorithm for the identification, counseling, … during the COVID-19 pandemic and beyond. 1 ." During pandemic, alternative telecare service is useful but there is a necessity for training and selection of subjects for telecare.…”
mentioning
confidence: 99%
“…Dear editor, we would like to share ideas on “The Role of the Smartphone in the Diagnosis of Vestibular Hypofunction: A Clinical Strategy for Teleconsultation during the COVID-19 Pandemic and Beyond. 1 ”. Barreto et al concluded that “ The creation of a digital vestibular management algorithm for the identification, counseling, … during the COVID-19 pandemic and beyond.…”
mentioning
confidence: 99%